2019
DOI: 10.1016/j.electacta.2019.06.087
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited tungsten-rich Ni-W, Co-W and Fe-W cathodes for efficient hydrogen evolution in alkaline medium

Abstract: The search of active, stable and cost-effective non-noble electrocatalysts for hydrogen evolution reaction (HER) is essential for sustainable energy systems. In this study, the electrodeposited Ni-W, CoW and FeW coatings having 5e30 at.% of W were examined as an alternative electrocatalysts for hydrogen evolution. The electrocatalytic efficiency of the electrodes was investigated on the basis of electrochemical data obtained from steady-state polarization technique in 30 wt% NaOH solution. It was found that wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 88 publications
1
22
0
1
Order By: Relevance
“…It is well known, that the broadening of the XRD peak is related to the refinement of the crystallite size that typically occurs with increasing the W content in the deposit. Indeed, the TEM analysis supported [5] that W-rich alloys have ultra-nanocrystalline structure composed of the grains with the size around 2-5 nm which is consistent with the grain size estimated from XRD results.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…It is well known, that the broadening of the XRD peak is related to the refinement of the crystallite size that typically occurs with increasing the W content in the deposit. Indeed, the TEM analysis supported [5] that W-rich alloys have ultra-nanocrystalline structure composed of the grains with the size around 2-5 nm which is consistent with the grain size estimated from XRD results.…”
Section: Resultssupporting
confidence: 86%
“…The mapping of elements, both iron group metal (Co, Ni, Fe) and W, indicated that metals are distributed almost evenly onto entire surface even at nanometric scale [5]. However, there are some regularly located spots with higher W amount.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, electrochemical studies were concentrated preferentially on Fe alloys, whereas the use of Ni, Co and their salts were discouraged due to environmental and health issues. Thus, Fe-W alloys as "eco-friendly" deposits are investigated for multipurpose applications: protective coatings [8], recording media [9,10], catalysts [11], and fuel cells [12].…”
Section: Introductionmentioning
confidence: 99%